Própolis em dieta à base de feno de Cynodon ssp fornecida para bubalinos - Costa Júnior, João Batista Gonçalves (2010)
It was evaluated the feed intake, the dry matter (DM) and nutrients total digestibility, ruminal characteristics and microbial efficiency in buffaloes fed with diet based on forage (70% of Cynodon spp hay and 30% of concentrate) with the addition of propolis based products (LLOS) in three concentrations (LLOSB3+, LLOSC1, LLOSC1+). Four crossbred buffaloes (Murrah ½ x ½ Jafarabadi), castrated, with 519.0 ± 13.0 kg were used in a 4x4 latin square with four treatments (Control, LLOSB3+, LLOSC1, LLOSC1+) and four periods. The diet was formulated to contain 60% of TDN and 11% of CP. The DM intake did not differ between the experimental diets. The addition of the LLOSC1 product increased (P <0.05) the coefficient of digestibility (CD) of DM (62,7% vs 67,2%), OM, NDF (56,6% vs 61,7%), CHT and TDN (62,8% vs 66,1%) . There was a tendency (P ? 0,10) for a higher CD of ADF (49,6% vs 56,5%), between the LLOSB3+ and the control diet. It was observed a significant effect of time and treatments (P <0.05) on ruminal pH, and the lowest pH (6.65) was obtained for LLOSC1 treatment. The LLOSC1 product provided higher production (P <0.05) of total VFA (141.89 vs 129.15) and trended (P ? 0.10) to a higher production of acetate (97.73 vs. 88.21 mM / mL) compared to the control. The ruminal dynamic variables and the efficiency of microbial synthesis (average of 9.85 g CPmic/100 g TDN) did not differ (P> 0.05) between treatments. Therefore, it is concluded that the product LLOSC1 may be indicated to improve the efficiency of diets based on forage for buffaloes.